Analisis Kebijakan Izin Tinggal Darurat Turis Asing Selama Pandemi COVID-19 Di Badung 2020 - Sri Janastri, Benedicta Virginia; Erawan, I Ketut Putra; Mahaswari J.M, A.A.Sagung Mirah (Jurnal Nawala Politika, 2022)
This study examines the controversy over the application of emergency residence permit imposed by the Government of Indonesia through Immigration Class 1 Ngurah Rai, during the Covid-19 Pandemic in Badung Regency. The aims of this study are to explain how this implementation was originally set up but caused controversy in Badung, to know about immigration authorities and embassies who are then represented by consulates in dealing with foreign tourists who are affected and cause problems. The findings in this study indicate that government regulations that provide free emergency stay permits for foreign tourists can actually cause problems. Meanwhile, with this issue, the role of immigration with the embassy represented by the consulate is very much needed. There is also a role for local communities in helping them.